Patients' experiences with technology during inpatient rehabilitation: opportunities to support independence and therapeutic engagement. (March 2014) - Fager, Susan Koch; Burnfield, Judith M.
Abstract Purpose: To understand individuals' perceptions of technology use during inpatient rehabilitation. Method: A qualitative phenomenological study using semi-structured interviews of 10 individuals with diverse underlying diagnoses and/or a close family member who participated in inpatient rehabilitation. Results: Core themes focused on assistive technology usage (equipment set-up, reliability and fragility of equipment, expertise required to use assistive technology and use of mainstream technologies) and opportunities for using technology to increase therapeutic engagement (opportunities for practice outside of therapy, goals for therapeutic exercises and technology for therapeutic exercises: motivation and social interaction). Conclusion: Interviews revealed the need for durable, reliable and intuitive technology without requiring a high level of expertise to install and implement. A strong desire for the continued use of mainstream devices (e.g. cell phones, tablet computers) reinforces the need for a wider range of access options for those with limited physical function. Finally, opportunities to engage in therapeutically meaningful activities beyond the traditional treatment hours were identified as valuable for patients to not only improve function but to also promote social interaction. Implications for Rehabilitation Assistive technology increases functional independence of severely disabled individuals. End-users (patients and families) identified a need for designs that are durable, reliable, intuitive, easy to consistently install and use. Technology use (adaptive or commercially available) provides a mechanism to extend therapeutic practice beyond the traditional therapy day. Adapting skeletal tracking technology used in gaming software could automate exercise tracking, documentation and feedback for patient motivation and clinical treatment planning and interventions.